Ex-post redistribution in a federation: implications for corrective policy - Marko Koethenbuerger (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper analyzes whether changes in the timing of equalizing transfers to state governments necessitate an adjustment in federal corrective policy. According to the existing literature (assuming an ex-ante choice of transfers), the corrective grant is equal to the marginal damage/benefit inflicted by externality generation. When the federal government accommodates state finances ex-post, the grant differs in formula from existing prescription. Allocative federal policy corrects state policy incentives twofold. It entails a correction for the distortion in the marginal benefit of state spending (as in earlier literature) and for the distortion in the marginal cost of public funds induced by the ex-post provision of transfers. The required grant rule is generically disproportionate to the equilibrium externality (even with lump-sum taxation). Furthermore, the ex-post provision of transfers is critical for the nature of the equilibrium inefficiency. Equalizing transfers at least partly internalize consumption spill-overs, but simultaneously establishes a new source of inefficiency. As a final result, the existing prescription for allocative federal policy continues to apply if the public good is pure.
Keywords: H7; D62; H3; H1; 330